Letter from Michael Kasha to Harrison Shull - Kasha, Michael A. (1957)
Concerns plans for nominating Robert S. Mulliken for the Nobel Prize in Chemistry.
Keywords: Kasha, Michael A., 1920-; Shull, Harrison; Mulliken, Robert Sanderson; Chemists; Herzberg, Gerhard, 1904-1999; Quantum chemistry; Barrow, Richard; Molecular spectra; Nobel Prize winners; Physicists; Chemistry, Physical and theoretical; Molecular theory; Diatomic molecules; Molecular structure